Local wisdom of To Cerekang customary law community in preservation of natural resources - Sulistianingsih, Erma; Hijjang, Pawennari; Busthanul, Nurbaya (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
One of the exciting and unique things about To Cerekang Customary Law Community is local wisdom in preserving natural resources. This research aims to analyze the form of local wisdom of To Cerekang Customary Law Community in preserving natural resources. The type of this research used a qualitative method with a phenomenological approach. Data was collected through in-depth interviews, observation, and documentation. The determination of informants is done by the purposive sampling technique. The results of the study indicated that the knowledge system of To Cerekang Customary Law Community includes knowledge of the forest; division of territory according to adat, collective ownership of the forest; forest ecology; protection of biodiversity; and knowledge of rivers. To Cerekang Customary Law Community in, preserving natural resources cannot be separated from the teachings of Batara Guru. The belief reinforces the conservation of natural resources in places that are considered sacred and customary rules that contain prohibitions, including the ban on entering the forest without Pua's permission, cutting down trees, polluting rivers, and killing crocodiles. Thus, the life of To Cerekang Customary Law Community has high respect for nature which is an inseparable part of their lives. Their respect for nature is interpreted as one of the tasks in life that comes from awareness and concern for preserving natural resources for the life of all creatures.